ADAPTATION TO CLIMATE CHANGE THROUGH SUSTAINABLE RICE CULTIVATION INNOVATION - Nurhayati; Ade Kurnia Sandi; Noverina Chaniago; Indra Gunawan; Mhd. Rizwan (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study aims to identify rice cultivation patterns and farmers' rice production responses to climate change by emphasizing the use of environmentally friendly technologies in Beringin District, Deli Serdang Regency, North Sumatra. A qualitative approach was conducted through interviews with ten farmers during the 2021–2023 period. The results show that all farmers have implemented the jajar legowo planting system—specifically the 4:1 pattern—as an environmentally friendly cultivation technology proven to improve land efficiency, lighting, and air circulation for plants. In addition, farmers consistently use organic fertilizers in the form of cow and goat manure, with doses adjusted annually to maintain soil fertility without polluting the environment. No use of inorganic fertilizers was found during the three years of observation. This strategy has proven effective, as indicated by an increase in yields from an average of 2.5 tons to 4.5–8 tons per farmer per planting season. These findings confirm that the application of environmentally friendly cultivation technologies not only increases productivity but also strengthens the resilience of agricultural systems in the face of climate change. This study recommends strengthening technical and policy support to expand the application of green technology in the agricultural sector.